Understanding Mycobacterium tuberculosis through its genomic diversity and evolution. - Mollie I Sweeney; Carson E Carranza; David M Tobin (PLoS Pathogens)
Pathogen evolution and genomic diversity are shaped by specific host immune pressures and therapeutic interventions. Analysis of the extant genomes of circulating strains of Mycobacterium tuberculosis, a leading cause of infectious mortality that has co-evolved with humans for thousands of years, can provide new insights into host-pathogen interactions that underlie specific aspects of pathogenesis and onward transmission. With the explosion in the number of fully sequenced M. tuberculosis strains that are now paired with detailed clinical data, there are new opportunities to understand the evolutionary basis for and consequences of M. tuberculosis strain diversity. This review examines mechanistic findings that have emerged from pairing whole genome sequencing data and evolutionary analysis with functional dissection of specific bacterial variants. These include improved understanding of secreted effectors that modulate the properties and migratory behavior of infected macrophages as well as bacterial genetic alterations important for survival within hypoxic microenvironments. Genomic, evolutionary, and functional analyses across diverse M. tuberculosis strains will identify prominent bacterial adaptations to their human hosts and shape our understanding of TB disease biology and the host immune response.